The Effect of the Gender and Culture of the IELTS Examiner on the Examinees' Performance on the IELTS Speaking Test in the UAE Context. - Altakhaineh, Abdel Rahman Mitib; AL-Tkhayneh, Khawlah M.; Rahrouh, Hanan N. (International Journal of Arabic-English Studies (IJAES), 2019)
This study examined the effect of the gender and culture of the IELTS examiner on the performance of Arab examinees on the IELTS speaking test. It relied on Communication Accommodation Theory to account for the linguistic behaviour of the examinees in reaction to the gender and the culture of the IELTS examiner. Through interviewing 15 female and 15 male IELTS examinees in Al Ain, the UAE and conducting focus group interviews with 10 IELTS teachers, the study showed that the two independent variables, i.e. the gender and culture of the IELTS examiners had different impacts on the examinees' performance on the IELTS speaking test. The results demonstrated that the gender of the IELTS examiner affected the performance of the Arab examinees in terms of preference. It also showed that the examiners' culture influenced the answers provided by the examinees who may not have been aware of certain cultural aspects related to the questions asked in the IELTS speaking test and vice versa. With respect to communication accommodation, the IELTS examinees' answers demonstrated a divergence tendency rather than a convergence one, reflecting a desire to establish social distance with the interlocutor, which may exhibit their strong feelings about their identity.